Nas vozes de um mesmo tempo: a educação física institucionalizada no período da ditadura militar em Cacequi - Rosa, Juliano de Melo da (2006)
This study is set as a proposal to the historical reestablishment about the institutionalized Physical Education in the municipal district of Cacequi during the period of the Dictatorial Military Government. It is an attempt to understand, locally, the role of the human movement in formal education inside a twenty one years of an authoritarian political system in the country, supporting then, an enlargement of the view we have today about the evolutionary process of this discipline. To approach such context, aiming at roughly cover the complex aspects that and investigation like this one includes, three work fronts were considered. These were a literature review from the official historical perspective about the Brazilian Military Dictatorial period, its influence in education and, specially in the institutionalized physical education; the use of the ideas like system, ecology of action and apparatus (based in Morin), which reveal complex aspects of life in society and, therefore, of the history constructing processes and; the use of Oral History as a means of conjugate and to expand the possibilities of approach and interpretation of the unleashed events specially by people who were involved with the formal Physical Education between 1964 and 1985 in Cacequi. In this way, considering a set of educational, cultural and political aspects portrayed in the narratives which gave some life to the discipline context during the military government, It was possible to perceive the presence of Physical Education as an element that propitiate something beyond the normalization of the society as wanted by the State, acting more in generating some level of autonomy and in the political formation of the individuals than on the contrary.